Hubungan antara Peran Pendidik Klinis dan Pelaksanaan Pendidikan Klinis dengan Tingkat Stres Mahasiswa - Siti Nova Romadhani; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Clinical education is an important aspect in health education, where students learn clinical skills in hospitals. The support of clinical educators and a conducive environment play a role in reducing stress. This study aims to analyze the relationship between the role of clinical educators and the implementation of clinical education with the level of stress of students during practice at RSI Sultan Agung Semarang. Using a quantitative method with a cross-sectional design, the population and sample in this study were 87 respondents with a total sampling technique. The results of the Spearman test showed a significant relationship with weak strength (p value 0.000), positive direction, and correlation coefficients of 0.471 and 0.514. Further research with a wider scope and qualitative methods is recommended to understand the factors causing student stress in more depth.